2021
DOI: 10.1094/mpmi-01-21-0016-a
|View full text |Cite
|
Sign up to set email alerts
|

ONT-Based Draft Genome Assembly and Annotation of Alternaria atra

Abstract: Species of Alternaria (phylum Ascomycota, family Pleosporaceae) are known as serious plant pathogens, causing major losses on a wide range of crops. Alternaria atra (Preuss) Woudenb. & Crous (previously known as Ulocladium atrum) can grow as a saprophyte on many hosts and causes Ulocladium blight on potato. It has been reported that it can also be used as a biocontrol agent against a.o. Botrytis cinerea Here we present a scaffold-level reference genome assembly for A. atra. The assembly contains 43 scaffol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Landraces normally are very genetically heterogeneous, so; are considered valuable sources of resistance to abiotic and biotic stresses to be exploited in the breeding programs (Casañas et In this study, we identi ed two distinct Alternaria species A. tenussima and A.atra attacking L.iberica which based on the pieces of literature are new for this host (Farr and Rossman, 2020). Both of them mainly are regarded as a saprophyte or as an opportunist plant pathogen (Simmons, 2007;Bonthala et al, 2021). As a plant pathogen, they show different host ranges, where 376 and 5 host plant species were infected by A.tenuissima and A. atra, respectively, and no record was observed for L.iberica (Farr and Rossman, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Landraces normally are very genetically heterogeneous, so; are considered valuable sources of resistance to abiotic and biotic stresses to be exploited in the breeding programs (Casañas et In this study, we identi ed two distinct Alternaria species A. tenussima and A.atra attacking L.iberica which based on the pieces of literature are new for this host (Farr and Rossman, 2020). Both of them mainly are regarded as a saprophyte or as an opportunist plant pathogen (Simmons, 2007;Bonthala et al, 2021). As a plant pathogen, they show different host ranges, where 376 and 5 host plant species were infected by A.tenuissima and A. atra, respectively, and no record was observed for L.iberica (Farr and Rossman, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Alternaria spp. are mainly saprophytes but some species obtaining pathogenic capacities changed to be very successful plant pathogens(Thomma, 2003;Bonthala et al, 2021).…”
mentioning
confidence: 99%
“…We also found that the abundance of Alternaria atra and Fusarium falciforme decreased in soil treated with a chitosan solution. These two fungal species cause diseases in several crops worldwide (Bonthala et al, 2021; Trolinger et al, 2017). Therefore, soil treatment with chitosan could be a sustainable alternative for managing these fungal plant pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…For the A. alternata isolate Z7, which causes brown spot of citrus, a high‐quality genome is available as well (Gai et al., 2021 ). A scaffold‐level genome assembly for Alternaria atra is available for an isolate that has been collected from a wild tomato plant (Bonthala et al., 2021 ). It has 43 scaffolds and a length of 39.6 Mb.…”
Section: Sequenced Genomesmentioning
confidence: 99%